PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP CYBERLOAFING PADA KARYAWAN GEN Z DI BANDAR LAMPUNG - Aulia Putri Nabila; Iskandar Ali Alam (MANAJEMEN DEWANTARA, 2026)
This study aims to determine the effect of job stress and workload, both partially and simultaneously, on cyberloafing among Gen Z employees in Bandar Lampung. Data collection was conducted through questionnaires distributed to 100 selected Gen Z employees in Bandar Lampung. The questionnaire consisted of 30 items with a 5-point Likert scale. The sampling method used in this study was probability sampling with the Lemeshow formula. Data analysis techniques used in this study included descriptive analysis, validity testing, reliability testing, classical assumption testing, hypothesis testing, and coefficient of determination testing, all processed using IBM SPSS Statistics version 26 software. The results showed that work stress and workload had a positive and significant effect on cyberloafing, both partially and simultaneously. These findings indicate that the higher the level of work stress and workload experienced by Generation Z employees, the higher their tendency to engage in cyberloafing behavior in the workplace.